Balancing Petroleum Policy : Toward Value, Sustainability, and Security - Huurdeman, Alexander; Rozhkova, Anastasiya (World Bank, Washington, DC, 2019)
Petroleum discovery in a country presents its policy makers with a challenging and complex task: formulating and agreeing on policies that will shape the country’s petroleum sector and guide the translation of the newly discovered resources into equitable and sustainable economic and social growth for the nation over the long term. Balancing Petroleum Policy provides policy makers and other stakeholders with the basic sector-related knowledge they need to embark on this task. It introduces a number of topics: the petroleum value chain and pivotal factors affecting value creation, a consultative process for developing a nation’s common vision on key petroleum development objectives, design of a legislative and contractual framework, petroleum fiscal regimes and their administration, prudent fiscal management, transparency and governance, environmental and social safeguards, and economic diversification through industrial linkages.